Transforming sugars into fat – lipid biosynthesis using different sugars in Yarrowia lipolytica. Issue 7 (20th April 2017) - Hapeta, Piotr; Rakicka, Magdalena; Dulermo, Remi; Gamboa‐Meléndez, Heber; Cruz‐Le Coq, Anne‐Marie; Nicaud, Jean‐Marc; Lazar, Zbigniew
Abstract: In an era of ever‐increasing energy demands, a promising technology is being developed: the use of oleaginous microorganisms such as Yarrowia lipolytica to convert waste materials into biofuels. Here, we constructed two Y. lipolytica strains that displayed both increased lipid accumulation and more efficient use of biomass‐derived sugars, including glucose, fructose, galactose and inulin. The first strain, Y. lipolytica YLZ150, was derived from the French wild‐type strain W29. It had inhibited triacylglycerol mobilization ( ∆tgl4 ) and β ‐oxidation ( ∆pox1–6 ), and it overexpressed GPD1, DGA2, HXK1, the native Leloir pathway, SUC2 from Saccharomyces cerevisiae and INU1 from Kluyveromyces marxianus . The second strain, Y. lipolytica Y4779, was derived from the Polish A‐101 strain. It had inhibited β ‐oxidation (∆mfe2 ) and overexpressed GPD1, DGA1, HXK1, YHT3, SUC2 and INU1 . In the first experiment, strain YLZ150 was batch‐cultured in media containing different hexoses; the highest values for lipid concentration and yield of lipids from the substrate were obtained using fructose (20.3 g dm −3 and 0.14 g g −1, respectively). In the second experiment, we grew the two strains in fed‐batch cultures to examine lipid biosynthesis from inulin (a fructose polymer). For Y4779, the lipid concentration was 10.3 g dm −3 and the yield of lipids from substrate was 0.07 g g −1 ; in contrast, for YLZ150, these values were 24 g dm −3 and 0.16 g g −1, respectively. The YLZ150 strain is thus able to efficiently exploit glucose, fructose, galactose, sucrose and inulin for lipid biosynthesis. Copyright © 2017 John Wiley & Sons, Ltd.